DAMPAK HUKUM PERKAWINAN DI BAWAH UMUR MENURUT HUKUM POSITIF DI INDONESIA - Sulikah, Siti (JURNAL LEGISIA, 2021)
Abstract: Underage marriage is a form of gender injustice experienced by women due to the strong roots of patriarchal culture in a society that considers women as goods and always under (subordination). Underage marriage is a complicated and sensitive issue. Therefore, this research was made with the aim of knowing the impact and legal consequences of underage marriage based on the provisions of Islamic law and the Marriage Law as well as other relevant laws and regulations in accordance with positive law in force in Indonesia. The legal writing method used is juridical-normative. The legal consequences of underage marriages have several legal and biological, psychological, social impacts and the impact of deviant sexual behavior. Keywords: Marriage, Underage, Positive Law